The Observatory Study On The Importance Of Controlled Environment Agriculture For Farmers, Consumers, And Policymakers - Dr. Hemachandran Ravikumar; Mrs Gunasundari Ramasamy; Dr Vasanthan G (Revista Electronica de Veterinaria, 1970)
Although its adoption is still hampered by technical and budgetary constraints, Abstract Controlled Environment Agriculture (CEA) offers a transforming solution for sustainable food production. Including 100 general public members and 100 specialists in the field, this study investigates the awareness, opinions, and difficulties related to CEA among 200 respondents. The results show that whereas ninety percent of the general public is aware of CEA, only thirty-six percent of experts in the field have actual experience and twenty-nine percent have theoretical understanding. While consumer concerns centre on the restricted variety of CEA-grown products (32%) and high costs (16%), major barriers to adoption are a lack of technical skills (42%) and high initial investment costs (30%). With 40% of professionals demanding government subsidies, 30% backing training programmes, and 50% of consumers favouring cost-reducing initiatives, policy support is clearly a major motivator for adoption. These findings imply that, even if CEA awareness is high, widespread implementation depends on overcoming budgetary constraints, bridging technical knowledge gaps, and resolving consumer scepticism. To improve CEA scalability, the paper advises public involvement campaigns, capacity-building projects, and financial incentives. Including these steps in agricultural policies will help to promote sustainable food production, boost market acceptance, and support world food security among difficulties related to climate change.